The femininization of Aids: knowledge of seropositive womenabout HIV-1 transmission and prevention - Gir, Elucir; Canini, Silvia R.M.S.; Prado, Marinésia A.; Carvalho, Milton J.; Duarte, Geraldo; Reis, Renata Karina (Brazilian Journal of Sexually Transmitted Diseases, 2004)
Introduction: FALTA Objective:to identify aspects related to ways of transmitting and preventing the human immunodeficiency virus (HIV) and report-ed by HIV seropositive women. Method:Data were collected by means of recorded semi-structured interviews, which were guided by a specific form.Result:most participants mentioned they did not know about HIV transmission and prevention modes before finding out about the infection diagnosis. It ishighlighted that 62% mentioned they did not know about the HIV transmission mechanisms, while 68% did not know about prevention measures. Amongthe possible ways of transmitting this virus, most women considered that vaginal and/or anal intercourse with condom is sufficient to prevent HIV trans-mission, and 12% of them did not consider oral sex a transmission way. Conclusion:it was concluded that, nowadays, there are still female HIV-1 patientswith unsafe sexual behavior who continue underestimating the infection. There is an urgent need for multiprofessional actions, not only with a view toinformation on HIV prevention and transmission, but also to elaborate a health education program that allows for discussions and the implementation ofactions able to give these women an active role in this process.